PENGARUH PEMELIHARAAN MESIN DAN TATA LETAK TERHADAP KELANCARAN PROSES PRODUKSI KOMPONEN ELEKTRIK PT. SHINHEUNG INDONESIA - Abdi Suci Wulandari; Erdi Erdi (Prosiding SEMANIS: Seminar Manajemen Bisnis, 2023)
PT. Shin Heung Indonesia is a company resulting from foreign investment (PMA) which is engaged in manufacturing electrical components and semiconductors, when producing electrical and semiconductor components, there are many obstacles that occur, one of which machines often experience damage due to routine use every day and working hours. engine that is long enough to cause the engine to work not optimally. This study aims to determine the maintenance of the machine and the layout of the smooth production process of electrical components PT. Shin Heung Indonesia. The population in this study were all production employees of the quality control division of PT. Shin Heung Indonesia with a total of 108 employees, the sampling the technique taken is saturated sampling (census). So that the sample used in this study amounted to 108 people. Based on the research results, engine maintenance has a positive and significant effect on the smooth production process of electrical components PT. Shin Heung Indonesia. The layout has a positive and significant effect on the smooth production process of the electrical components of PT. Shin Heung Indonesia. Simultaneously, the variables of machine maintenance and layout have a positive and significant effect on the smooth production process of the electrical components of PT. Shin Heung Indonesia